Cross-reaction of cytokines in cetacean snap frozen tissue sections - Jáber Mohamad, José Raduán; Pérez, J.; Alves Godinho, Ana; Caballero Cansino, María José; Andrada Borzollino, Marisa Ana; Fernández Rodríguez, Antonio Jesús (2007)
The understanding of the role of different cytokines during inflammatory diseases could lead to better knowledge of the marine mammal immune system. This study evaluates the cross-reactivity of a panel of ten monoclonal antibodies to human and bovine cytokines in snap frozen tissue sections of lung, spleen, liver and mesenteric lymph nodes of three species of cetaceans: Atlantic spotted dolphins (Stenella frontalis), striped dolphins (Stenella coeruleoalba) and fin whale (Balaenoptera physalus). In serial sections, anti-human CD3, IgG, and lysozyme polyclonal antibodies (pAbs) were used to labels T and B cells, and macrophages/monocytes respectively. The anti-human IL-1α, IL-1β, IL-2, IL-6, IL-8, IL-10, TNF-α, CD25 and anti-bovine IL-4 and IFN-γ mAbs yielded immunolabelling in cetacean snap frozen lymph node tissue sections similar to that obtained in the species of origin, but they did not react in formalin-fixed tissue sections. The anti-human CD3, IgG, and lysozyme pAbs reacted both in formalin-fixed and snap frozen tissue sections of the three cetacean species. Macrophages and lymphocytes were the most common cell population immunolabelled with the anti-cytokine mAbs. The results of the present study suggest that this panel of anti-cytokine mAbs may be useful to evaluate cytokine expression in snap frozen tissue samples of the species of cetacean tested. This is of interest because all these antibodies could be used to evaluate the immune status in these animals, testing cytokine expression in several pathological processes, such as bacterial, viral, parasitic or toxic diseases